PENGARUH DISIPLIN KERJA, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PASMIRA GRESIK - Isvan Sholahuddin Febrianto; Maulidyah Amalina Rizqi (Lafadz Jaya Publisher, 2023)
This research is motivated by the company's performance that cannot run well because all actions taken in each activity are determined by employees who are members of the company. Employees are the main driver of all company activities, as well as to maintain its existence, the company starts a business to manage human resources, especially in increasing work effectiveness and efficiency to the maximum so that the company's goals can be achieved at Pasmira Gresik. This study aims to explain the effect of work discipline, motivation and work environment on employee performance at Pasmira Gresik. This research is a research with a quantitative approach. The location of this research is Pasmira Gresik. The variables in this study are work discipline, motivation, work environment. The population in this study were the employees of Pasmira Gresik. The sample in this study were 83 employees of Pasmira Gresik. The sampling technique is the Probability Sampling Technique or Simple Random Sampling. The data collection technique used is by distributing questionnaires. The data analysis technique used multiple linear regression analysis techniques. The results showed that work discipline, motivation and work environment had a positive and significant effect on employee performance at Pasmira Gresik.